2001
DOI: 10.1179/136217101101538541
|View full text |Cite
|
Sign up to set email alerts
|

Microresistance spot welding of Kovar, steel, and nickel

Abstract: Microresistance spot welding of 0.2–0.5 mm thickness Kovar, steel, and nickel using different types of power supply was investigated. The effects of process parameters (welding current/pulse energy, electrode force, and welding time/pulse width) on joint strength and nugget diameter were studied. The maximum values of welding current and nugget diameter that did not result in weld metal expulsion and/or electrode–sheet sticking were determined. The difference between micro- and ‘large scale’ resistance spot we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
22
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 56 publications
(22 citation statements)
references
References 5 publications
0
22
0
Order By: Relevance
“…[1,5,6] This is especially true in resistance microwelding because of the relatively low values of welding current, electrode force, and resistivities of nonferrous workpieces. [4,7] It is generally considered that, in resistance cross-wire welding, "set down," an indication of the extent to which the wires Q ϭ I 2 Rt are compressed into each other, can be used to evaluate joint strength. [1] For example, Moravskii et al, [8] in an investigation of resistance cross-wire microwelding of various fine wires using a capacitor-discharge power supply, found that 30 to 35 pct setdown produced good joint quality, while Stroev et al [3] observed an optimum setdown of 30 to 50 pct in a similar investigation, but on nickel lead-outs of 0.2 mm in diameter.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[1,5,6] This is especially true in resistance microwelding because of the relatively low values of welding current, electrode force, and resistivities of nonferrous workpieces. [4,7] It is generally considered that, in resistance cross-wire welding, "set down," an indication of the extent to which the wires Q ϭ I 2 Rt are compressed into each other, can be used to evaluate joint strength. [1] For example, Moravskii et al, [8] in an investigation of resistance cross-wire microwelding of various fine wires using a capacitor-discharge power supply, found that 30 to 35 pct setdown produced good joint quality, while Stroev et al [3] observed an optimum setdown of 30 to 50 pct in a similar investigation, but on nickel lead-outs of 0.2 mm in diameter.…”
Section: Introductionmentioning
confidence: 99%
“…The resistance includes contact resistance at the electrode/workpiece and workpiece/workpiece interfaces and bulk resistance of the base materials. [4] Among these resistance components, the workpiece/workpiece contact resistance, which is influenced mainly by material properties (such as hardness and resistivity), surface characteristics (such as cleanliness and roughness), and electrode force, may be the most important factor affecting the process. [1,5,6] This is especially true in resistance microwelding because of the relatively low values of welding current, electrode force, and resistivities of nonferrous workpieces.…”
Section: Introductionmentioning
confidence: 99%
“…The solder in electronics [18] has the main goal to ensure a good electrical connection between the parts to be welded [19][20][21]. It is also important and necessary to ensure a rigid mechanical, sturdy and long-lasting connection between the two metal surfaces.…”
Section: Introductionmentioning
confidence: 99%
“…[5 -8] In resistance welding, a weld is formed between two metal sheets through the localized melting and coalescence of a small volume of the material(s) at the faying interface due to resistance heating generated by the passage of electric current. [5] However, the welding current will also degrade the electrode tip surfaces due to the resistance heating at the electrode/sheet interfaces. Little work has been published on electrode tip degradation mechanisms and engineering solutions in microresistance welding.…”
Section: Introductionmentioning
confidence: 99%